Sistem Otomasi Proses Likuifikasi dalam Pembuatan Setengah Jadi Gula Cair Dari Ubi Singkong - Dedi Sanzay Sirait; Yuliati Yuliati; M. Hadi Santosa (Widya Teknik, 2020)
Sugar is a simple carbohydrate that becomes the main source of energy and trading commodity. Sugar is used to turn the taste into sweetness and the state of food or drink. Domestic sugar production is still not meeting domestic needs. Technologically the manufacture of glucose syrup is relatively simple and can be done by small or medium industrie. In this research will be done design equipment production process of liquid sugar made from cassava raw that can be developed by small industries. Making liquid sugar made from cassava is expected to be an alternative source of fructose. This tool is designed to be made using stainless stell material, and using arduino uno as its control center, umun how this tool works is a pH meter probe and Resistance Temperature Detector produces a measurable resistance value and received by the signal pondisi frame. If arduino uno detects a change in the measurable voltage value and does not match the limits of alkaline acid and temperature then the arduino will run the base acid pump and heating regulator